Association between abnormal lipid metabolism and tumor - Li, Chunyu; Wang, Fei; Cui, Lili; Li, Shaoxin; Zhao, Junyu; Liao, Lin (Frontiers in Endocrinology, 2023)
Metabolic reprogramming is a sign of tumor, and lipid, as one of the three major substances, has an obvious impact. Abnormal lipid metabolism is related to many diseases, and the proportion of people with abnormal lipid metabolism is increasing year by year. Lipid metabolism is involved in the occurrence, development, invasion and metastasis of tumors by regulating various tumorigenic signal pathways. The difference of lipid metabolism in different tumors is related to tumor origin, regulation of lipid metabolism pathway, diet and other factors. In this paper, the lipid synthesis pathway and the research progress between cholesterol, triglyceride, sphingolipid, ester raft, lipid regulating drugs and tumors are reviewed, and the limitations of current research and potential tumor therapeutic targets and drugs in the lipid metabolism pathway are pointed out. The study and intervention of abnormal lipid metabolism may provide new ideas for tumor treatment and survival prognosis.